On second order wave loading and response in irregular seas - R Eatock Taylor; M.P. Kernot (World Scientific, 1999)
Wave drift responses at low frequencies and springing at high frequencies can both be modelled as second order processes involving terms proportional to the square of the wave elevation in irregular seas. Although the models of both these phenomena share many common features, springing introduces several additional complexities. These concern both the second order hydrodynamic analysis, and the probabilistic modelling of the resulting first plus second order response. This article highlights these in the context of springing, which is particularly relevant to the design of Tension Leg Platforms and offshore structures susceptible to lightly damped resonant responses, at periods in the range from around 2 to 5 seconds. The three closely linked aspects of hydrodynamics, spectral analysis and probabilistic modelling are considered, and sample numerical results discussed.